Pengaruh Digitalisasi Perbankan Terhadap Kepuasaan Mahasiswa Pengguna Layanan Digital Bank Syariah (Studi Pada Mahasiswa UMP) - Ariska Putri Mase; Artika Sari Devi; Nur Ainun; Rezky Ramadhani; Sulfitra M; Suraidah Sarbia (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the effect of banking digitalization on student satisfaction at Muhammadiyah Palopo University. This research uses a quantitative method where the population used is all UMP students and the sample consists of 30 samples. This research uses Simple Random Sampling Technique. And using primary data in the form of a questionnaire. The research results show that there is an influence between the Banking Digitalization variable (X) on Student Satisfaction (Y). By implementing banking digitalization, the bank believes it can be compared and has the best responsiveness to customer (student) needs. Based on the data analysis that has been carried out in this research, it can be concluded that there are benefits or positive effects of using digital banking at Sharia Banks on student satisfaction. Currently, customers (students) are used to using digital banking.